The Design and Visual Assets Two-dimension Educational Game “Infinity Of Kuku” By Using Pixel Art Style - Johannes Latuny (Universitas PGRI Yogyakarta, 2023)
Abstract The Design and visual assets are the most important part of a game. The two-dimension educational game design with Pixel Art styling can provide players a nostalgic impression as well as the understanding of the game. This educational game aims to increase the players' interest in learning, in order that the substance of the research object Kutus-Kutus Oil, can be claimed explicitly. An Infinity Of Kuku game is designed to provide effectiveness and profit of each composition of Kutus-Kutus Oil which is made from 69 composites of various plants. Moreover, it can increase immunity and remedy the body from all kind of diseases together with Covid-19. The method used in this study is the Game Development Life Cycle (GDLC). The analysis has attained an Alpha Testing phase under the engineer and team using Game Maker 8.1 tool. The result of the trial are relevant with the primary concept which is organized within Game Design Document (GDD). Keywords : Educational Game Design, 2D, Pixel Art, Kutus-Kutus Oil, GDLC